Speciation of heavy metals in water from the Uganda side of Lake Victoria - Mbabazi, Jolocam; Twinomuhwezi, H.; Wasswa, J.; Ntale, M.; Mulongo, G.; Kwetegyeka, J.; SchrǾder, K.H. (International Journal of Environmental Studies, 2010)
Different forms of copper Cu, zinc Zn, lead Pb and cadmium Cd in water from the Uganda side of Lake Victoria (25°C, pH 6.75–7.18), the second largest inland freshwater lake in the world, have been studied using ion-exchange, dialysis and atomic absorption spectrophotometry. The results indicate that heavy metals Cu, Zn, Pb and Cd are present mainly in the cationic form (80–83%). Small quantities of anionic (13–22%), non-ionic, dialyzable (4–8%), and non-ionic, non-dialyzable (< 1.3–4.4%) forms were also detected for all metals except Cd. The corresponding concentrations lay in the ranges: cationic, 0.06–0.99; anionic, < 0.001–0.25; non-ionic, dialyzable, < 0.001–0.08; non-ionic, non-dialyzable, < 0.001–0.06 μg ml−1. The existence of the metals in non-ionic and nondialyzable forms is attributable to metal associations with high relative molecular mass (RMM) organic matters.
Keywords: Heavy metals; Speciation; Dialysis; Ion-exchange; Lake Victoria; Atomic absorption spectrophotometry